ANALISIS SWOT PENGGUNAAN CHAT GPT DALAM DUNIA PENDIDIKAN ISLAM - Yasmar, Renti; Amalia, Dian Risky (Fitrah, 2024)
Chat GPT is an artificial intelligence tool that has sparked debate regarding its implications for the world of education. Researchers use a qualitative method with a SWOT analysis framework approach to describe the strengths and weaknesses of ChatGPT, as well as discuss its opportunities and threats to Islamic education. Its strengths include the use of advanced natural language models to generate reasonable answers, the ability to improve itself, and the provision of personal and real-time responses. Thus, ChatGPT can enhance access to information, facilitate personalized and complex learning, and reduce the teaching workload, making processes and tasks more efficient. Its weaknesses include a lack of deep understanding, difficulty in evaluating the quality of responses, the risk of bias and discrimination, and a lack of high-level thinking skills. The threats to education include a lack of contextual understanding, threatening academic integrity, promoting discrimination in education, democratizing plagiarism, and the decline of high-level cognitive skills.